What is the true discharge rate and pattern of the striatal projection neurons in Parkinson’s disease and Dystonia? - Dan Valsky; Shai Heiman Grosberg; Zvi Israel; Thomas Boraud; Hagai Bergman; Marc Deffains (eLife, 2020)
Dopamine and striatal dysfunctions play a key role in the pathophysiology of Parkinson’s disease (PD) and Dystonia, but our understanding of the changes in the discharge rate and pattern of striatal projection neurons (SPNs) remains limited. Here, we recorded and examined multi-unit signals from the striatum of PD and dystonic patients undergoing deep brain stimulation surgeries. Contrary to earlier human findings, we found no drastic changes in the spontaneous discharge of the well-isolated and stationary SPNs of the PD patients compared to the dystonic patients or to the normal levels of striatal activity reported in healthy animals. Moreover, cluster analysis using SPN discharge properties did not characterize two well-separated SPN subpopulations, indicating no SPN subpopulation-specific (D1 or D2 SPNs) discharge alterations in the pathological state. Our results imply that small to moderate changes in spontaneous SPN discharge related to PD and Dystonia are likely amplified by basal ganglia downstream structures.